THE COVERAGE OF PSYCHOLOGICAL HEALTH IN THE WORKS OF YUSUF HAS HAJIB - Nuriddinov Rasuljon Samitjon ugli (Bright Mind Publishing, 2025)
The article examines "Kutadgu Bilig," considered one of the first works in the Turkic language by the medieval Eastern thinker and statesman Yusuf Khas Hajib. The work "Kutadgu Bilig" is not only a collection of political and moral teachings, but also rich in views on personal development, inner balance, and psychological health. The thoughts and ideas put forward in the work can be considered as "basic principles of psychological health" in modern psychology.
Keywords: Knowledge leading to happiness, happiness, Ozgurmish, Ogdulmish, justice, Kuntugdi, period of harmony.